Development of an IoT-Based Home Security System Prototype Using Multisensors and ESP32-CAM - Jumita Nannung; Alimuddin Sa'ban Miru; Muliadi; Gunawan (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
Advancements in information technology have driven the development of home security systems based on the Internet of Things (IoT). This study aims to design a home security system using ESP32-CAM, multisensors, and Telegram for real-time monitoring. The system features face recognition using the Haar Cascade and LBPH algorithms, along with DHT22 and MQ-2 sensors to monitor temperature, humidity, and hazardous gases. The development method used is the prototype model. Testing results showed a face recognition accuracy of 95.31% and the ability to detect temperatures above 40°C and gas concentrations exceeding 300 PPM. The system performs optimally at a distance of 35–150 cm but is limited by extreme lighting and facial angle variations. In conclusion, the system enhances home surveillance effectiveness through real-time monitoring and reliable remote access control